Discovering Auctions: Contributions of Paul Milgrom and Robert Wilson. (8th July 2021) - Teytelboym, Alexander; Li, Shengwu; Kominers, Scott Duke; Akbarpour, Mohammad; Dworczak, Piotr
Abstract: The 2020 Sveriges Riksbank Prize in Economic Sciences in Memory of Alfred Nobel was awarded to Paul R. Milgrom and Robert B. Wilson for "improvements to auction theory and inventions of new auction formats". In this survey article, we review the contributions of the laureates, emphasizing the subtle interplay between deep theoretical questions and practical design challenges that resulted in one of the most successful fields of economics.